Game Elements towards More Sustainable Learning in Object-Oriented Programming Course - Jusas, Vacius; Barisas, Dominykas; Jančiukas, Mindaugas (Sustainability, 2022)
Gamification of education is considered to have the capacity to increase students’ engagement in a learning process; to drive learning and skills acquisition; and creates changes for more sustainable behavior. Sustainable behavior is especially important in studying the initial courses at a university. Object-oriented programming (OOP) is such a course in the studies for a programmer’s diploma. We applied four elements of gamification: experience points, interactive content, local team, and global team. A local team is dedicated specifically to the OOP course, but all other game elements can be applied to any course. The course was implemented in a Moodle platform, where two additional plugins for experience points and interactive content were employed. Research using the implemented gamified course in the teaching process was carried out during the fall semester in 2020 and results compared to two previous non-gamified course years. A statistically insignificant increase in the mean grade was observed. Nevertheless, the gamified course resulted in a 7% decrease in the number of students who had to retake the OOP course compared to the year 2019. The gamified course also resulted in a drastic decrease in the number of students requiring a second attempt to pass the course’s exam. The obtained results demonstrate that the gamification of OOP course resulted in more sustainable behavior of the students. Based on the results of students’ questionnaires, we highly recommend using global team game element as it showed a positive effect on students’ engagement when the number of participating students is large.